THE IMPROVEMENT OF WRITING ACHIEVEMENT BY USING PICTURES FOR NINTH GRADE STUDENTS OF PRIMAGAMA KARANG PLOSO MALANG - SUKMAWATI, NI LUH AYU (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Writing Achievement, Pictures, Writing skill, Ninth grades, Primagama Karang Ploso Malang. The writer aims to improve students’ writing achievement by using pictures in writing descriptive text for the ninth grade students of Primagama Karang Ploso Malang. This study used Classroom Action Research (CAR) for research design. The data in this research was obtained from the students’ descriptive writing products. The descriptive writing products were descriptive text written by the ninth grade students of the second semester in Primagama Karang Ploso. The writer found the improvement of writing achievement by using picture of writing descriptive text for ninth grader students of Primagama Karang Ploso